2017
DOI: 10.3390/ijms18010157
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagic Degradation Process Contributes to Claudin-2 Expression Increase and Epithelial Tight Junction Dysfunction in TNF-α Treated Cell Monolayers

Abstract: Tight junction dysfunction plays a vital role in some chronic inflammatory diseases. Pro-inflammatory cytokines, especially tumor necrosis factor alpha (TNF-α), act as important factors in intestinal epithelial tight junction dysfunction during inflammatory conditions. Autophagy has also been shown to be crucial in tight junction function and claudin-2 expression, but whether autophagy has an effect on the change of claudin-2 expression and tight junction function induced by TNF-α is still unknown. To answer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Remarkably, the activation of autophagy could impair the barrier function of Caco-2 monolayers through down-regulating the expression of ZO-1, occludin and claudin-1, up-regulating claudin-2 expression, and destroying the morphology of both ZO-1 and occludin. Similarly, inhibition of autophagic degradation process was reported to contribute to epithelial tight junction dysfunction in TNF-α treated cell monolayers [48]. However, autophagy was demonstrated to enhance tight junction through down- [19].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the activation of autophagy could impair the barrier function of Caco-2 monolayers through down-regulating the expression of ZO-1, occludin and claudin-1, up-regulating claudin-2 expression, and destroying the morphology of both ZO-1 and occludin. Similarly, inhibition of autophagic degradation process was reported to contribute to epithelial tight junction dysfunction in TNF-α treated cell monolayers [48]. However, autophagy was demonstrated to enhance tight junction through down- [19].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, autophagy was reported for the first time to regulate intestinal barrier function via inducing lysosomal degradation of the tight junction protein CLDN2 (claudin 2), thus decreasing epithelial permeability [10]. Increased CLDN2 level and tight junction defects in intestinal epithelial Caco-2 monolayers treated with the pro-inflammatory cytokine TNF/TNFA (tumor necrosis factor) partly arises from the inhibition of autophagy-mediated CLDN2 degradation [11] ( Figure 1A). It was recently shown that defects in mitochondria and ER functions induce intestinal permeability, promoting E. coli internalization and transcytosis across the epithelium, and these are counteracted by selective autophagy-mediated elimination of intracellular bacteria, which is so-called xenophagy [12].…”
Section: Autophagy and Intestinal Epithelial Barrier Functionmentioning
confidence: 99%
“…Atg16l1 ΔIEC mice infected with murine norovirus and then treated with dextran sulfate sodium (DSS) exhibit exacerbated pathological score and increased nonapoptotic epithelial cell death compared to control mice [15]. Moreover, the viability in response to TNF treatment of intestinal organoids carrying the CD-associated ATG16L1 T300A variant is [10,11]. (B) Defective autophagy leads to intestinal dysbiosis and increased IgA-coated bacterial amount [26,27,32].…”
Section: Autophagy and Epithelial Cell Deathmentioning
confidence: 99%
“…Next, to monitor the effect of EGCG on autophagy in live cells, we transfected 4T1 cells with an adenovirus expressing the m-Cherry-GFP-LC3B fusion protein (Ad-mCherry-GFP-LC3B). 20 Under normal conditions, the mCherry-GFP-LC3B protein disperses in the cytoplasm and displays homogeneous yellow fluorescence. When the autophagic process is triggered, the mCherry-GFP-LC3B will gather around at the membrane of the autophagosome, and yellow dots appear.…”
Section: Egcg Induces Autophagy In Breast Cancer Cellsmentioning
confidence: 99%